SERANGGA PENGUNJUNG BUNGA ACACIA VILLOSA WILLD. - SIH KAHONO; L.E. PUDJIASTUTI; M. AMIR (BERITA BIOLOGI, 1987)
SIH KAHONO, L.E. PUDJIASTUTI &. M. AMIR. 1987. Insect visitors on Acacia villosa Willd. Suppl. Berita Biologi. 3 : 70 - 71 Insect visitors on Acacia villosa Willd. (Leguminosae) has been observed at 10 flowering plants at Cibinong, Bogor. Observation were made at 6 a.m.-6 p.m. by means of collecting insects that visit the flowers of A. villosa for 30 minute with the interval time collection of 2 hours.There were found Hymenoptera (17 species), and followed by Lepidoptera (7 species) and Diptera (3 species).The community sturcture of the insect visitors at interval of 2 hours are varies, the number increased toward the mid day, and gradually declined in the evening. This fluctuation is probably due to the nectar content during the day.